1994
DOI: 10.1101/gad.8.13.1561
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of alternative pre-mRNA splicing by a novel repeated hexanucleotide element.

Abstract: The alternatively spliced exon EIIIB is regulated in a cell type-specific manner in the rat fibronectin gene. Splicing of EIIIB into fibronectin mRNA is dependent on sequences in the intron immediately downstream of EIIIB. We show that a short, highly repeated TGCATG motif in this intron is important for cell type-specific recognition of EIIIB as an exon. This motif enhances usage of the EIIIB 5' splice site; furthermore, this repeated TGCATG sequence can activate an alternatively spliced exon in the unrelated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
171
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(178 citation statements)
references
References 72 publications
7
171
0
Order By: Relevance
“…The sequence motif involved in nonsense-mediated mRNA decay is another example of a short RNA repeat involved in posttranscriptional regulation. Short RNA sequences that modulate both mRNA turnover and splicing have been identified (10,27,33,34,36,37,63,68,73,74,77). As with the results presented here, sequences flanking these motifs can influence their activity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The sequence motif involved in nonsense-mediated mRNA decay is another example of a short RNA repeat involved in posttranscriptional regulation. Short RNA sequences that modulate both mRNA turnover and splicing have been identified (10,27,33,34,36,37,63,68,73,74,77). As with the results presented here, sequences flanking these motifs can influence their activity.…”
Section: Discussionmentioning
confidence: 66%
“…A region in the c-fos 3Ј-UTR that is distinct from the AU-rich element and can increase the activity of either a wild-type or mutant form of the AU-rich element has been identified (12). A short RNA repeat in the alternatively spliced exon EIIIB of the rat fibronectin gene regulates its cell type expression (36). Both the cell type specificity and the degree of splicing are affected by the sequences flanking the RNA repeat (36).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that cells are variable in their use of the individual regulatory elements is underscored by the two triple repeat elements+ The triple UGCAUG element activated splicing most strongly in LA-N-5 cells with lower effects in N1E115 and HeLa cells+ This element has also been shown to affect splicing of the fibronectin and nonmuscle myosin transcripts (Huh & Hynes, 1994;Kawamoto, 1996;Lim & Sharp, 1998)+ In contrast, the triple GGGGGCUG element combined with the purine rich exonic element enhanced splicing most strongly in HeLa and N1E115 cells but only weakly in LA-N-5+ Although the whole enhancer functions in all the cells, the importance of any single element in the enhancer evidently depends on the cell type being examined+…”
Section: Cell Type Specificity and Combinatorial Control Of Splicingmentioning
confidence: 99%
“…Alternative pre-mRNA splicing is a common means of gene regulation in eukaryotes that allows the generation of multiple protein isoforms from a single gene (for reviews see Wang & Manley, 1997;Y+ Wang et al+, 1997)+ The control of pre-mRNA splicing pattern can be very precise and there are many examples of exons in mammalian cells whose inclusion is highly tissue specific+ A variety of pre-mRNA sequence elements and regulatory proteins are known to affect the splicing patterns of different RNA transcripts+ Although these regulatory components must ultimately alter spliceosome assembly at certain splice sites, the interactions between the general splicing apparatus and its regulators are mostly unknown+ In particular, the molecular events that determine the tissue-specific use of an exon in mammalian cells have not been described+ One difficulty in understanding the precise nature of an exon's regulation is the diversity of mechanisms that can affect its splicing+ Splicing enhancer elements activate the use of splice sites that are otherwise ignored by the general splicing machinery (Hertel et al+, 1997;Wang & Manley, 1997), whereas repressor sequences are thought to block recognition of certain splice sites+ The tissue-specific expression of a particular splicing pattern often depends on a combination of positive and negative control+ Splicing enhancers can be classified by their location in either exons or introns+ These two types of enhancer are thought to be mechanistically different and to bind different types of regulatory proteins+ Exonic splicing enhancer sequences are often bound by a group of factors called SR proteins (Fu, 1995;Chabot, 1996;Manley & Tacke, 1996;Valcarcel & Green, 1996;Caceres & Krainer, 1997)+ Proteins in the SR family contain one or two RNA binding domains of the RRM type and a C-terminal domain rich in serine-arginine dipeptides+ SR proteins are essential for constitutive splicing and also play an important role in the selection of alternative splice sites+ In particular, SR proteins bound with other factors to exonic splicing enhancers are thought to promote spliceosome assembly to upstream 39 splice sites, although the mechanism for this effect on splicing is not yet clear (Wang et al+, 1995;Zuo & Maniatis, 1996; Rudner et al+, 1998)+ In contrast to ex-onic enhancers, intronic splicing enhancers are often found in introns downstream of regulated exons, and have not been shown to bind SR proteins (Balvay et al+, 1992;Black, 1992;Huh & Hynes, 1994;Del Gatto & Breathnach, 1995;Sirand-Pugnet et al+, 1995;Carlo et al+, 1996;Kawamoto, 1996;…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the exonic, purine-rich elements described above, a number of splicing enhancers are found within introns (Gooding et al+, 1994;Huh & Hynes, 1994;Del Gatto & Breathnach, 1995;Gallego et al+, 1997;Wei et al+, 1997;Carstens et al+, 1998;Kosaki et al+, 1998;Lim & Sharp, 1998;Lou et al+, 1998;McCarthy & Phillips, 1998;Chou et al+, 1999)+ The sequences of intronic splicing enhancers identified thus far are diverse and often distinct from the purine-rich splicing enhancers+ Consistent with the differences in sequence, proteins bound to intronic splicing enhancers are usually different from the SR proteins that bind purine-rich enhancers+ The activity of splicing enhancers may be regulated by the nature and amount of specific RNAbinding proteins within the cell nucleus+ Other variables are also likely to be important, including the locations of multiple enhancer and repressor elements, and the strength and position of adjacent or competing processing sites+ Characterization of such regulatory elements is important for understanding the mechanisms regulating alternative pre-mRNA processing+…”
Section: Introductionmentioning
confidence: 99%